The Training Model of Teachers Within the Sector of Gifted Education, a Research in Latin America - Almazán-Anaya, Andrew; Almazán-Anaya, Dafne (Revista Electrónica Educare, 2021)
Introduction. The education of gifted students in Latin America is still developing; it includes the training process of its professors, a key aspect in the success of specialized schools. Objective. The objective was to conduct a four-year qualitative study with teachers, students, and principals to describe and analyze the teacher training process for gifted students in one of the largest differentiated (specialized) schools in Latin America. Method. The methodology was qualitative with interviews and field observation for four years; during this period, we developed a descriptive guide for each step of the training process based on member checking, triangulation, verification, and checking against the existing literature. Results. Six stages of teacher education were described, which resulted in obtaining a general panorama of how the teachers within gifted schools get trained in a developing country, where formal and accredited processes of teacher formation have not been fully implemented yet. These findings showed strengths and weaknesses in the formative stages of teachers in this special environment that allow keeping in operation special educational centers for gifted students in schools in Latin America. These findings also created an evidence-based guide for the training of future teachers in schools with gifted students, especially when there is no formal training process available locally.